2020
DOI: 10.1101/2020.02.24.963264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional insights from biophysical study of TREM2 interactions with ApoE and Aβ1-42

Abstract: INTRODUCTION:TREM2 is an innate immune receptor expressed on myeloid cells including microglia in the brain. How TREM2 engages different ligands remains poorly understood. METHODS: We used comprehensive BLI analysis to investigate the TREM2 interactions with ApoE and monomeric amyloid beta (mAβ42). RESULTS: TREM2 binding did not depend on ApoE lipidation, and there were only slight differences in affinity observed between ApoE isoforms (E4 > E3 > E2). Surprisingly, diseaselinked TREM2 variants within a "basic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 56 publications
(96 reference statements)
3
31
0
Order By: Relevance
“…Crucially, however, we also found that wild-type sTREM2 inhibits the formation of fibrils and larger Aβ oligomers and disaggregates protofibrils and larger Aβ oligomers into the smallest Aβ oligomers. This is consistent with a recent, preliminary report ( 30 ) that WT sTREM2 inhibited Aβ aggregation, measured by thioflavin T assay. In contrast, we found that R47H sTREM2 promoted the formation of Aβ protofibrils, indicating a gain of function by this mutation.…”
Section: Discussionsupporting
confidence: 93%
“…Crucially, however, we also found that wild-type sTREM2 inhibits the formation of fibrils and larger Aβ oligomers and disaggregates protofibrils and larger Aβ oligomers into the smallest Aβ oligomers. This is consistent with a recent, preliminary report ( 30 ) that WT sTREM2 inhibited Aβ aggregation, measured by thioflavin T assay. In contrast, we found that R47H sTREM2 promoted the formation of Aβ protofibrils, indicating a gain of function by this mutation.…”
Section: Discussionsupporting
confidence: 93%
“…TREM2 polymorphism causes structural changes in the receptor, leading to a partial loss of its function. However, the role of TREM2 in neurodegeneration and AD remains unclear [107].…”
Section: Trem2 and Alzheimer's Pathogenesismentioning
confidence: 99%
“…Amyloid plaque formation is a primary diagnostic measure of Alzheimer's disease with both APOE and TREM2 linked to amyloid deposition (2,4,9,40,48,67,70,71). For example, TREM2 can bind amyloid, altering microglial function, linking the TREM2-APOE pathway directly to amyloid-driven disease progression (72,73). Loss of functional Trem2 in mice resulted in plaques that contained reduced amounts of APOE and promoted amyloidogenesis in mice by reducing microglial function (71,74) indicating that microglia, through TREM2 mediated signaling, can regulate APOE co-deposition around amyloid deposits.…”
Section: Discussionmentioning
confidence: 99%